Fuentes de fósforo enriquecidas con cachaza y microorganismos en la microbiota del suelo, la absorción de fósforo y la caña de azúcar en la producción de materia seca - Hernández, Alfredo R.; de Prado, Renato M. [UNESP]; Castellanos González, Leónides; Caione, Gustavo; Moda, Leandro R. [UNESP]; Assis, Luis C. [UNESP]; Almeida, Hilário J. [UNESP] (My University, 2015)
Filter cake enriched with biofertilizer (associated with fertilizer phosphate) can increase the available phosphorus, and thus improve the absorption of phosphorus and dry matter accumulation by plants. The objective of this study was to evaluate the effect of phosphorus sources in the absence and presence of filter cake (enriched with biofertilizer or not enriched) on the soil population of microorganisms, soil phosphorus content, phosphorus accumulation in the aerial portion of the plant and production of dry matter in sugar cane plants. The experiment was performed in a greenhouse using sugar cane as the test plant. A completely randomized design was adopted with a 3×3+1 factorial arrangement and three repetitions. The treatments consisted of the application of three phosphorus sources (50 mg dm-3 of P, soluble in citric acid), (i.e., triple superphosphate, reactive phosphate of Bayóvar® and natural phosphate of Araxá), combined with three filter cake treatments (enriched/not enriched with biofertilizer and no filter cake as a control). The experimental unit consisted of a pot (20 dm3) filled with samples of an Oxisol soil containing two plants. Ninety days after the transplantation, samples were evaluated in terms of the soil phosphorus content and the populations of bacteria, fungus and phosphate solubilizer microorganisms. After one hundred and twenty days, the production of dry mass and accumulation of phosphorus were evaluated. The triple superphosphate associated with filter cake enriched with biofertilizer stood out relative to the use of cake only in terms of increasing the phosphorus content in the soil, the phosphorus accumulation in the plant and the dry mass production in sugar cane plants.
Phosphorus sources enriched with filter cake and microorganisms in the soil microbiota: Phosphorus absorption and sugar cane dry matter production
Keywords: Agricultural waste; Organic-fertilizer; Phosphate fertilizer; Saccharum spp